Exploring Students’ Perceptions of Science Laboratory Practices: A Comparative Study Between Rural and Urban Schools - Dwiningsih, Safrida; Lestari, Ina; Ismi, Roma; Rahmadina, Sri Wahyu; Sinaga, Masdalena; Rahmad, M. (Sekolah Pascasarjana Universitas Negeri Malang (UM), 2025)
This study aims to analyze students' perceptions of the implementation of science laboratory practicums at public middle school 020 Pekanbaru and public middle school 7 Pangkalan Kuras, Riau Province. Using a quantitative survey method, this study involved 75 student respondents. The instrument used was a questionnaire consisting of 26 statements, analyzed descriptively. The results show that students' perceptions of the preparation, implementation, and conclusion stages of the practicum fall into the